Interpolymer Complexes Based on Carbopol® and Poly(2-ethyl-2-oxazoline) as Carriers for Buccal Delivery of Metformin - A. S. Viktorova; E. S. Elizarova; R. S. Romanova; V. R. Timergalieva; V. V. Khutoryanskiy; R. I. Moustafine (Разработка и регистрация лекарственных средств, 2021)
Introduction. Buccal drug delivery has a number of advantages over oral administration: ease of application, good blood supply to the buccal mucosa, drug can enter the systemic circulation directly, avoiding the "first pass effect through the liver", and are not exposed to the acidic environment of the gastric juice and the destructive action of digestive enzymes. The use of interpolymer complexes (IPCs) makes it possible not only to ensure adhesion to the mucosal membranes of the oral cavity, but also to achieve a prolonged release of drugs.Aim. Development of carriers based on interpolymer complexes using Carbopol® 971 NF (C971) and poly(2-ethyl-2-oxazoline) (POZ) of different molecular weights for buccal delivery of metformin (MF).Materials and methods. The study of IPC adhesion was carried out using a TA.XTplus texture analyzer (Stable Micro Systems, UK); mucin compacts with a diameter of 13 mm were used as a substrate; these were prepared by compressing porcine gastric mucin powder using a manual hydraulic press for IR spectroscopy (PerkinElmer, USA) at a pressure of 2.45 MPa. The study of the swelling capacity was carried out by placing polymer matrices in an artificial saliva medium, with constant thermostating at a temperature of 37.0 ± 0.5 °C for 5 hours. The study of the release of MF from the matrices based on IPC was carried out using a DFZ II apparatus (Erweka, Germany) according to the Flow Through Cell method (USP IV) with cells for tablets (22.6 mm) and adaptors for ointments, creams and gels in a medium simulating saliva. The concentration of MF in the samples from the dissolution tests was determined with UV-spectrophotometry (Lambda, PerkinElmer, USA) at 232.8 nm.Results and discussion. In a comparative study of the mucoadhesive properties of polymer samples, IPC compacts showed a mucoadhesion capacity comparable to that of poly(2-ethyl-2-oxazoline); at the same time, compacts from physical mixtures (PM) and C971 are inferior in terms of the separation force to IPC samples, however, POZes dissolve in an artificial saliva medium, that is, they are not suitable as dosage forms for buccal delivery. For 5 hours of the experiment to assess the swelling capacity, the IPC matrices did not change significantly, which can ensure their comfortable use as carriers for buccal delivery. When evaluating the release of metformin from polymer matrices (with weight ratio MF/IPC 1: 0.5), the most complete release (more than 90 %) is observed from both IPC matrices compared to matrices of PM and individual polymers.Conclusion. Polycomplex matrix systems based on C971-POZ (50 kDa) and C971-POZ (500 kDa) are suitable for buccal delivery of metformin.